Organothiol‐Based Hybrid‐Layer Strategy for High‐Performance Copper Adhesion and Stress‐Migration via Simultaneous Oxide Reduction. Issue 14 (13th April 2016) - Xiao, Qiran; Watson, Brian L.; Dauskardt, Reinhold H.
Abstract : The presence of defective native copper‐oxide (Cux O) remains a challenge for device technologies owing to its detrimental effects on the adhesion, moisture sensitivity and stress‐migration. Here we demonstrate a rapid, single‐step, and organic‐solvent‐free sol‐gel deposition process that is capable of simultaneously reducing the weak native Cu‐oxide while forming a densely connected Cu/hybrid interface. A marked 9‐fold improvement in adhesion is reported, along with a substantial decrease in the Cu stress‐migration rate during in‐situ isothermal stress‐relaxation experiments. The enhanced Cu/hybrid interface adhesion and the improved Cu stress‐migration performance were attributed to the partial reduction of the ~2 nm native Cu2 O layer as demonstrated via atomic‐resolution transmission electron microscopy. The hybrid‐layer strategy we developed is expected to be effective in not only being a strong candidate for adhesion improvement to Cu, but in promoting Cu stress‐ and the related electro‐migration performance. Abstract : The presence of defective native Cu‐oxide remains a challenge for device technologies. Here, a rapid, single‐step, and organic‐solvent‐free sol–gel deposition process is demonstrated that acts by simultaneously reducing the weak Cu‐oxide while forming a densely connected Cu/hybrid interface. A marked ninefold improvement in adhesion is reported, along with a substantial decrease in the Cu stress‐migration rate during in situ isothermal stress‐relaxation experiments.